Sports Journalism in Growing Platforms: Analyzing Soccer Broadcasting in Twitch through LaLiga Casters - Marín-Sanchiz, Cristian Ramón; Valero-Pastor, José María; Rojas-Torrijos, José Luis (Estudios sobre el Mensaje Periodístico, 2022)
Twitch has established itself as the digital platform of reference for the distribution of audiovisual content. In this environment, traditional sports journalism has experienced a big growth. With the aim to delve into this trend, this research performs a case study about LaLiga Casters, an official series of game streaming led by Spanish content creator Ibai Llanos, through the analysis of its content and a survey of heavy users (n=50). From a practical point of view, it is possible to determine that these broadcasts have broad similarities with traditional radio and television programs. However, the first steps of a process of media convergence can be observed: while users of traditional sports broadcasts can follow the matches with a more casual tone at certain times, such as the post-game, Twitch streamers increase the journalistic quality of their content thanks to typical procedures of legacy media.